2011
DOI: 10.1016/j.hkpj.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isolytic contraction and passive manual stretching on pain and knee range of motion after hip surgery: A prospective, double-blinded, randomized study

Abstract: Stretching has its impact on both contractile and noncontractile tissues and is the most important rehabilitation technique utilised used to prevent and treat joint stiffness. Passive manual stretch (PMS) and muscle energy technique (MET) are two of the most commonly used techniques. Our study evaluates the effectiveness of isolytic form of MET in gaining knee range of motion (ROM) and decreasing pain in acute knee involvement and comparing it with standard PMS. We used the clinical scenario of knee joint mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The study concluded that MET was more effective than stretching in improving hamstring flexibility [19]. A study by Parmar et al [20] concluded that isolytic contraction was better in improving range and reducing pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that MET was more effective than stretching in improving hamstring flexibility [19]. A study by Parmar et al [20] concluded that isolytic contraction was better in improving range and reducing pain.…”
Section: Discussionmentioning
confidence: 99%
“…MET is an advanced stretching techniques [7]. Studies using these two techniques individually in symptomatic as well as in asymptomatic population have shown improvement [8–12], but very few studies have compared these techniques in a symptomatic population, where conflicting results are seen [1320]. A study done by Mahajan et al [17] compared these two treatment technique in patients with mechanical neck pain.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that MET was more effective in improving knee ROM in patients who had restricted knee ROM in the acute duration in post-operative hip fractures. 3 No adverse reactions were documented with application of MET in the immediate post-operative period in this study. Hence, it is safe to use MET in the early stages of fracture rehabilitation.…”
Section: Discussionmentioning
confidence: 62%
“…This plays a role in the descending modulation of pain. 3 On application of MET, there maybe a reduction in proinflammatory cytokines and it may also desensitize the peripheral nociceptors. Blood and lymphatic flow rates may also be affected due to rhythmic muscle contraction and there could be changes in the interstitial pressure and increase in the transcapillary blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation